2016
DOI: 10.1097/qai.0000000000001184
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Operational Research: Active Referral of Children of HIV-Positive Adults Reveals High Prevalence of Undiagnosed HIV

Abstract: Objectives Few routine systems exist to test older, asymptomatic children for HIV. Testing all children in the population has high uptake but is inefficient, while testing only symptomatic children increases efficiency but misses opportunities to optimize outcomes. Testing children of HIV-infected adults in care may efficiently identify previously undiagnosed HIV-infected children before symptomatic disease. Methods HIV-infected parents in HIV care in Nairobi, Kenya were systematically asked about their chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 26 publications
3
36
4
Order By: Relevance
“…In the tPITC group, we found an HIV positivity rate (case detection rate/yield) of 3.5%, which was closer to the 4.0% but lower than the 7.4% reported by Saeed et al in Malawi [ 15 ] and Wagner et alin Kenya [ 16 ], respectively. The HIV prevalence (4.3%) in the general population in Cameroon (4.3%) [ 17 ] is lower compared to Malawi (9.2%) and Kenya (5.4%) [ 8 ] and this may explain the lower HIV positivity rate observed among the pediatric and adolescent population in our study compared to Malawi and Kenya as reported in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In the tPITC group, we found an HIV positivity rate (case detection rate/yield) of 3.5%, which was closer to the 4.0% but lower than the 7.4% reported by Saeed et al in Malawi [ 15 ] and Wagner et alin Kenya [ 16 ], respectively. The HIV prevalence (4.3%) in the general population in Cameroon (4.3%) [ 17 ] is lower compared to Malawi (9.2%) and Kenya (5.4%) [ 8 ] and this may explain the lower HIV positivity rate observed among the pediatric and adolescent population in our study compared to Malawi and Kenya as reported in the aforementioned studies.…”
Section: Discussionsupporting
confidence: 63%
“…In our study, according to the parents’ declarations, the main reasons for their inability to return to the hospital with their children for HIV testing included the lack of transport fare (38.3%), children not living with them (25.6%), and the lack of time (10.5%). These reasons should be taken with caution because the HIV testing uptake could have also been limited by parental’ levels barriers, notably fear of self-disclosure, stigma and discrimination as reported by previous studies [ 4 , 16 , 20 22 ]. There is a need for qualitative research to provide in-depth information on parental barriers to the uptake of HIV testing for children in the context of tPITC approach implementation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The entry point for HIV testing in children influences the proportion of cases found [16][17][18]. A study by Wagner et al conducted in Nairobi, Kenya, where HIV-infected adults were encouraged to bring their children for HIV testing (family index testing), found that the rate of pediatric HIV testing increased 3.8-fold from 3.5% to 13.6% [16]. A similar study by Lewis Kulzer et al conducted in the Nyanza province in Kenya reported that HIV testing through the family index approach increased case detection among children [17].…”
Section: Discussionmentioning
confidence: 99%
“…HIV testing offered to children or sexual contacts of individuals living with HIV) is anticipated to have higher uptake and yield compared to universal HIV testing approaches. When implemented in Malawi, Kenya, Lesotho and Cameroon, index-linked testing for children did result in a higher yield of HIV (proportion of eligible children who test positive) compared to universal testing, but uptake of testing (proportion of eligible children tested) remained suboptimal, ranging from 14 to 71% [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%